Analysis of Relationships Between Intellectual Capital and Measurement Performance Indicators of the Pharmaceutical Companies in Tehran Stock - Javadi, Hadi Kord; Kohandel, Zahra; Fardi, Khadije (Ciência e Natura, 2015)
Intellectual Capital is the most precious possession of companies in modern economy; therefore, Intellectual Capital of industrial centers is ever-increasingly changing to become the chief indicators both in company operations and in improving its ability to manage the organization capitals. In the main, the current study aims to investigate the relationship between the Intellectual Capital and performance measurement. In this research, the independent variable is the intellectual capital having three dimensions of human, structure and physical capitals, and the dependent variable is the organization operation with two dimensions of economical and accounting which are going to be assessed in this study. The Statistical population is the pharmaceutical companies admitted in the Tehran Stock Exchange from 1387 to 1391 amounting to 30 companies in total. This research investigates the time span from the beginning of 1387 up to the end of year, 1391. Data relevant to variables has been collected by the software of the Stock Exchange. The collection of data has been carried out by means of SPSS. In this study, the researcher used the descriptive and inferential statistics (Spearman test) and the results show that the hypotheses are as follows 1. There is statistical significance between intellectual capital and performance measurement, 2. There is no statistical significance between the intellectual capital and ROR of the owners’ salary, 3. There is no statistical significance between the intellectual capital and the ROR of the properties, 4. There is statistical significance between the intellectual capital and the value added of the market, 5. There statistical significance between the intellectual capital and economic value added.